Room Temperature Detection of Acetone by a PANI/Cellulose/WO3 Electrochemical Sensor. (8th January 2018) - Aparicio-Martínez, Eider; Osuna, Velia; Dominguez, Rocio B.; Márquez-Lucero, Alfredo; Zaragoza-Contreras, E. Armando; Vega-Rios, Alejandro
Abstract : Chemical sensing based on semiconducting metal oxides has been largely proposed for acetone sensing, although some major technical challenges such as high operating temperature still remain unsolved. This work presents the development of an electrochemical sensor based on nanostructured PANI/cellulose/WO3 composite for acetone detection at room temperature. The synthesized materials for sensor preparation were polyaniline (PANI) with a conductivity of 13.9 S/cm and tungsten trioxide (WO3 ) in monoclinic phase doped with cellulose as carbon source. The synthesized materials were characterized by high resolution transmission electron microscopy (HRTEM), X-ray diffraction (XRD), cyclic voltammetry (CV), and Raman spectroscopy. The composite was applied for acetone detection in the range of 0 to 100 ppmv at room temperature with electrochemical impedance spectroscopy (EIS) for monitoring resistance changes proportional to acetone concentration. The developed sensor achieved a calculated limit of detection of 10 ppm andR 2 of 0.99415 with a RSD of 5% (n = 3 ) at room temperature. According to these results, the developed sensor is suitable for acetone sensing at room temperatures without the major shortcomings of larger systems required by high operating temperatures.